Design of Rainfall Intensity Measuring Instrument Using IoT-Based Microcontroller - Nofri Wandi Al-Hafiz; Helpi Nopriandi; Harianja (Universitas Islam Kuantan Singingi, 2024)
The design of a rainfall intensity measuring device utilizing an Internet of Things (IoT)-based microcontroller aims to offer a more precise, efficient, and real-time solution for rainfall measurement compared to the traditional manual systems. While manual systems are still commonly used, they have significant limitations, including reliance on human observation, slow response times, and measurement inaccuracies. In this study, the designed tool incorporates a tipping bucket rain sensor connected to an ESP32 or ESP8266 microcontroller and a Wi-Fi module to transmit real-time data to a cloud-based IoT platform. The collected data is processed and visualized through graphs accessible via web or mobile applications. This system facilitates continuous rainfall monitoring and provides fast, accurate information that can be applied to disaster mitigation, agricultural planning, and natural resource management. By leveraging IoT technology, this system addresses the shortcomings of manual methods, offering considerable benefits for more timely and data-driven decision-making.